Margin Analysis and Marketing Efficiency of Patchouli Oil in Wonua Sangia Village Landono District South Konawe District - Tahyat, Muhammad Aswan; Rosmawaty, Rosmawaty; Yusran, Yusran (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2022)
This research aims to analyze margins and efficiencies for each marketing agency. This research was conducted in Wonua Sangia Village, Landono District, South Konawe Regency. This study was conducted from June 2021 to March 2022. Thes objects in the study were patchouli farmers in Wonua Sangia village of Landono Subdistrict and patchouli oil marketing agencies. The sample in this study was done by purposive sampling method for patchouli farmers and Snowball Sampling for fishing institutions. Their search was analyzed using margin analysis and marketing efficiency. This study showed two patchouli oil marketing channels in Wonua Sangia Village, Landono Subdistrict. Marketing channels (I), Farmers, Middlemen, Collecting Merchants, Wholesalers, and Consumers. Then Marketing channels (II), Farmers, Collecting Merchants, Wholesalers, and Consumers. Marketing channel II has the highest Farmer's Share value of 81%, with a total marketing margin of IDR97.000/kg. It is indicated to have the best marketing efficiency of a channel, 80%, with a total marketing margin of IDR110.000/kg. Both marketing channels have been efficient because the farmer's share value obtained>50%.